Academic Performance vs. Academic Persistence: A Study of Black Students' Perceived Personal Competency - Robbie J. Steward; James D. Jackson (Educational Considerations, 1990)
The present study examines the contribution of Black students' perceived personal competencies to both a four-year academic persistence and freshman GPA.